Karakteristik Bioplastik dari Pati Buah Lindur (Bruguiera gymnorrizha) - Johan Budiman; Rodiana Nopianti; Shanti Dwita Lestari (Jurnal FishtecH, 2018)
This research studied the characteristics of bioplastic from large-leafed mangrove (Bruguiera gymnorrizha) starch. This research was arranged used Randomized Block Design (RBD) model, with different starch concentration (0.5%, 1%, 1.5% and 2%) as treatment. The parameters observed were mechanical properties (tensile strength and percent elongation), thickness, water uptake and biodegradation test. The result showed that the starch concentration was not significant, (P>0.05) affected tensile strength and water resistance. Different between treatments was observed as for elongation, thickness and biodegradation test significant (P<0.05). The results obtained from the bioplastic research of large-leafed mangrove starch for tensile strength ranged from 24.59 MPa – 32.91 MPa, percent elongation 2.93% – 4.88%, thickness 0.05 mm – 0,11 mm, water resistance 108.06% – 111.09% and biodegradation test with percent weight loss 17.91% – 54.40% with the highest degradation rate 18.13 – 3.62 mg /15 days burial. The best treatment was obtained by using 1,5% starch, 4 g chitosan and 15% glycerol or equal to starch : chitosan 1.5 g : 4 g and 0.9 mL glycerol.